Cloning and Expression of Recombinant Human Interleukin-7 in Chinese Hamster Ovary (CHO) Cells - Toghraie, Fatemeh Sadat (Rep Biochem Mol Biol, 2017)
BACKGROUND: The critical role of interleukin-7 (IL-7) in homeostatic proliferation and T cell survival has made it a promising cytokine for the treatment of various clinical conditions, especially those associated with lymphopenia. METHODS: In the present study we expressed recombinant human interleukin-7 (rhIL-7) in Chinese hamster ovary (CHO)-K1 cells. CHO-K1 cells were stably transfected with both circular and linear forms of the pBud-hIL-7 recombinant by electroporation. Expression of rhIL-7 in CHO-K1 cells was confirmed by enzyme-linked immunosorbent assay (ELISA) and dot and western blots. RESULTS: On western blots of transformed cells, a single 25 kDa band was observed, consistent with the expected molecular weight of glycosylated hIL-7. No significant expression difference was observed between cells transfected with circular or linear plasmids. CONCLUSION: We established a stable CHO-K1 cell line expressing rhIL-7, which we consider to be a promising system for the production of rhIL-7 as a biopharmaceutical.